987 VENTRICULAR TACHYCARDIA CATHETER ABLATION: THE ROLE OF ARRHYTHMIA INTERRUPTION DURING RADIOFREQUENCY EROGATION. (15th December 2022) - Luciani, Lara; Volpato, Giovanni; Valeri, Yari; Compagnucci, Paolo; Falanga, Umberto; Cipolletta, Laura; Parisi, Quintino; Rita, Enrico; Guerra, Federico; Casella, Michela; Dello Russo, Antonio
Abstract: Background: Due to the complexity of the underlying substrate and to the difficulty in characterizing the arrhythmia mechanism and circuitry, every ventricular tachycardia (VT) catheter ablation (CA) represents a challenge. Nowadays VT CA is an increasingly recommended and used procedure. Objective: Investigate whether VT interruption during radiofrequency (RF) delivery can be regarded as a marker indicating a lower risk VT recurrence at follow-up. Methods: We conducted a retrospective cohort study and we enrolled 69 patients with VTs treated with CA using RF energy, from November 2018 to July 2022. First, in all patient substrate and late potential map was performed; than VT induction was attempted. In patients in whom activation mapping could be performed, we first targeted VT interruption, followed by substrate modification (fragmented/late potential elimination and/or dechanneling of the entire pathologic zone) [group1]. In 15 patients, it was not possible to perform activation mapping due to the poor hemodynamic VT tolerance and/or to the absence of VT inducibility with programmed ventricular stimulation. In these cases, substrate CA was performed, aiming to eliminate fragmented and/or late potentials [group2]. Recurrences were assessed with ICD in office interrogations and remote monitoring for a median of 12 (IQR 5-20) months of follow-up. Results: Sixty-nine patients were included in the study. Respectively for the group1 and for the group2, the mean age at baseline was 60 ± 18, 3 and 63 ± 12, 3 p > 0, 05) and the mean left ventricular ejection fraction was 41, 3 ± 12, 6% and 38, 2 ± 11, 8% (p > 0, 05). In 41 (59%) patients, the indication for the procedure was electrical storm refractory to pharmacological therapies or multiple ICD shocks due to VT/VF. 12 (17%) patients underwent endo-epicardial CA due to the presumed epicardial VT origin and only 9 (13%) underwent right ventricular CA. Among the 31 patients in which it was possible to interrupt the arrhythmia through RF delivery, we observed 9 (23%) sustained VT recurrence at follow-up. Among the 38 patients in which VT was not interrupted with RF delivery or the VT had poor hemodynamic tolerance, there were 16 (42%) sustained VT recurrences at follow-up. Risk of recurrence at follow-up was numerically lower in patients in which VT was interrupted with RF delivery during the procedure, but not statistically significant (p value > 0, 05). Conclusions: In patients undergoing CA for VTs, activation mapping is useful to enhance the understanding of the arrhythmia circuitry. Our preliminary results seem to suggest that VT interruption during RF delivery may represent a positive prognostic marker, pointing to better outcomes and lower recurrence rates, even if the results were not statistically significant. Further investigations with a larger cohort of patients is required to confirm these findings.